Similarity Analysis of Klebsiella pneumoniae Producing Carbapenemases Isolated from UTI and Other Infections - Agata Pruss; Paweł Kwiatkowski; Monika Sienkiewicz; Helena Masiuk; Agnieszka Łapińska; Barbara Kot; Zuzanna Kilczewska; Stefania Giedrys-Kalemba; Barbara Dołęgowska (Antibiotics, 2023)
Klebsiella pneumoniae is an important opportunistic pathogen responsible for severe infections, mainly urinary tract infections (UTIs) and pneumonia. Hospital epidemic infections caused by multiresistant strains of carbapenemase-producing K. pneumoniae are the most concerning. NDM-producing strains are resistant to a wide range of antibiotics and have become the most significant threat. Determining the natural reservoirs and routes of infections is essential to end hospital outbreaks. Understanding the relatedness of K. pneumoniae strains is essential to determine the range and nature of the infection. The study compared phylogenetic relatedness between multiresistant K. pneumoniae strains isolated from hospitalized patients. Susceptibility to drugs and mechanisms of resistance were confirmed using phenotypic methods. PFGE was used to analyze the relatedness between strains. We analyzed 69 K. pneumoniae strains from various healthcare units. The isolates were mainly identified from urine. Strains were resistant to β-lactam antibiotics with β-lactamase inhibitors, cephalosporins, and quinolones. Their susceptibility to aminoglycosides and carbapenem antibiotics was diverse. Most of the isolated strains produced New Delhi metallo-ß-lactamase (NDM). Although K. pneumoniae strains were classified into several genotype clusters, closely related isolates were confirmed in the same hospital’s wards, and in two hospitals in the same province.